Stress-dependent permeability measurement techniques for unconventional gas reservoirs: Review, evaluation, and application. (15th November 2019) - Feng, Ruimin; Chen, Shengnan; Bryant, Steven; Liu, Jun
Highlights: Various permeability measurement techniques are summarized. Pulse decay methods for permeability tests under stressed conditions are reviewed. Analytical solutions for transient pressure data interpretation are derived. A comparison between different pulse decay methods is made through numerical modeling. Factors that influence the accuracy of the measured permeability are analyzed. Abstract: The assessment of economic viability on unconventional gas reservoir formations has been challenging due to the difficulties in accurately quantifying their permeabilities in the micro-/nano-Darcy range. Core plugs are commonly used for stress-dependent permeability measurements using the pulse decay method (PDM). However, the resultant permeabilities from different PDMs are full of controversy because of the variability in the measured permeabilities. Such variability results from the different analytical solutions used for measured data interpretation. An in-depth review is provided on permeability measurement techniques, including the steady-state and various unsteady-state methods. By comparison, it is concluded that the PDMs are the best option when performing permeability measurements under in-situ stress/strain conditions. The review highlights seven different PDM techniques, the mathematical models closely representing each PDM technique are established and their analytical solutions are then derived for experimental data interpretation. Recently emerged PDM techniques are reviewed for the purpose of achieving fast permeability measurements. These PDM techniques involve two different gas flow scenarios: axial flow and radial flow in core samples. In the review we describe each method's advantages and disadvantages, and it was found that fast permeability measurements can be achieved by the radial flow PDMs. We analyzed multiple factors which could influence the accuracy of the measured permeability, and revealed that the reservoir volumes, pulse sizes and sample preparation could be the dominant ones. This study sheds lights on the limitations and suitability of each PDM technique and provides a better way to interpret experimental data and achieve fast measurements.